Understanding Subgenual Cingulate Functional Connectivity in Major Depressive Disorder Using 7T Fmri - Laith Alexander; Mu Li; James Murrough; Laurel Morris (BJPsych Open)
Aims: We aimed to determine differences in subgenual anterior cingulate cortex (sgACC) resting-state functional connectivity (rsFC) in Major Depressive Disorder (MDD) vs. healthy volunteers (HV) using 7-Tesla functional magnetic resonance imaging (fMRI). Abnormalities in the sgACC are linked to MDD, but the sgACC is anatomically and functionally diverse, including Brodmann area (BA) 25 (Cg25) and the subgenual portion of area 32 (Cg32). The differences in rsFC between Cg25 and Cg32 in MDD compared with HVs have not been directly examined. High-resolution 7T fMRI offers an unrivalled opportunity to measure differences in rsFC between these two subregions which otherwise suffer from signal dropout.